Metacognitive deficits in major depressive disorder - Hong, Shuning; Chi, Mengjiao; Chen, Haisi; Chu, Fengfeng; Zheng, Yuping; Tao, Ming (Frontiers in Psychiatry, 2025)
ObjectiveWe aimed to investigate the metacognition of patients with major depressive disorder (MDD) and its correlation with their condition, as well as explore its diagnostic significance in the early stages of the disease, thereby providing a reference for clinical treatment.MethodsUsing a cross-sectional research design, we selected 66 patients diagnosed with MDD and 99 healthy controls for a mental rotation task; we examined their metacognitive performance using a post-decisional confidence assessment paradigm. We evaluated various aspects, including their performance on first-order tasks (d’), metacognitive bias (average confidence), metacognitive sensitivity (meta-d’), metacognitive efficiency (the M Ratio).ResultsIn terms of the first-order task performance (d’), the group with MDD scored significantly lower than the healthy controls (t = -4.274, p < 0.001, respectively). Regarding metacognitive bias(average confidence), metacognitive sensitivity (meta-d’), and metacognitive efficiency (the M ratio), the group with MDD performed significantly worse than the healthy controls (t = -4.280, p < 0.001; t = -3.540, p < 0.001; t = -2.104, p = 0.039, respectively). In addition, the Hamilton Rating Scale for Depression (HAMD-17) scores of the patients with MDD were significantly negatively correlated with their d’, average confidence levels, meta-d’, and M ratio(r = -0.468, p < 0.001; r = -0.601, p < 0.001;r = -0.457, p < 0.001; r = -0.362, p = 0.003), The average confidence levels of MDD patients are significantly positively correlated with d’, meta-d’, and M ratio. (r = -0.552, p < 0.001; r = 0.738, p < 0.001;r =0.273, p =0.02).ConclusionThe metacognitive abilities of patients with MDD were significantly impaired, and the degree of metacognitive impairment was related to the severity of clinical depressive symptoms. Moreover, the impairment of their metacognitive abilities was correlated with negative metacognitive bias.Clinical Trial Registrationhttps://www.chictr.org.cn, identifier ChiCTR2400091242